Edwards elliptic curves. Comparison of cryptographic libraries - Melnykova, O.; Dzhuryk, O.; Masliennikova, A. (Radiotekhnika, 2018)
Edwards Curves is a form of representing elliptic curves that supports fast, unified, and complete law of addition of points. Edwards curves have attracted great interest for their efficient addition and doubling formulas. In this paper, we described and compared programming libraries, which implemented Edwards curves and EdDSA signature.